Enhancement of Lipid and Biomass Production in Microalgae Scenedesmus abundans by Microwave Irradiation: Life Sciences-Biotechnology - Kapavarap, Bhanu Rajarajeswari; Kotikalapudi, Sree Rama Chandra Karthik; Oruganti, Krishna Keerthika; Bodiga, Sreedhar; Bodiga, Vijaya Lakshmi; Veeravilli, Suryanarayana; Poda, Sudhakar; Vemuri, Praveen Kumar (International Journal of Life Science and Pharma Research, 2022)
Due to the rising depletion of fossil fuels and increased energy demands, human society is looking for clean sustainable energy. Commercially produced algal biodiesel is limited by the expense and difficulty of oil extraction and subsequent biodiesel conversion technologies. Microalgae with high oil content are only alternatives for decreasing fossil fuel supplies, but more work remains to be done to improve the lipid content of microalgae strains. In this study, strain improvement is done using microwave radiation in Scenedesmus abundans to increase the production of triacylglycerol, which is the main source of biodiesel. Microalgal cultures were exposed to varied microwave irradiation over different time periods. Under microwave irradiation, 20-25 mins reaction time seems suitable for the complete in situ transesterification reaction. Microwave heating transesterification has been shown to be more effective for adequate biodiesel yield compared to the conventional transesterification process. Maximum increase of 2.22-fold in biomass, and 2.5-fold in triacylglycerol was observed for microwave irradiation of 25 mins and 20 mins intervals respectively. The percentage of some monounsaturated fatty acids increased in gas chromatographic examination of neutral lipid fractions from total lipids of microwave irradiated samples, is considered as one of the preferable properties of biodiesel. According to our study findings, Scenedesmus abundans qualifies as the most efficient feedstock for biodiesel production, and microwave-assisted in situ transesterification reduces the requirement for a large amount of solvents, longer reaction times, and high reaction temperatures and pressures.